Risk terrains of illicit drug activities in Durham region, Ontario - Onat, Ismail (Canadian journal of criminology and criminal justice, 2018)
Street-level drug activities pose a serious problem for communities, and exploring the environmental context of drug crimes is one important aspect of the increasing problem in Canada. This study examined the urban backcloth of illicit drug activities in the Durham Region, Ontario. Drawing on the locations of 5,297 drug arrests between 2011and 2013, along with 6,291 surrounding physical features in the environment, the risk terrain modelling framework guided the analyses, which revealed that the risk of drug crimes varies by context and time. Similar to previous research in the United States and the Netherlands, the authors found that 11 out of 18 correlates were significantly associated with drug crimes. Unlike other study settings, the locations of alcohol sales and service did not predict the occurrence of drug crimes in the Durham Region. In addition, the risk clusters differed when the same correlates were modelled for incidents of each year separately. The models provided a valid prediction from one year to the next. Nearly 85% of all places with illicit drugs arrests in 2012 and 2013 overlapped with high-risk places of 2011 and 2012, respectively. The resulting risk map informs practitioners and policy makers on where to focus resources in the region.